2006
DOI: 10.1016/j.aanat.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain composition of tongue muscle in microphthalmic (mi/mi) mice before and after weaning

Abstract: running title: MyHC in tongue muscle of mi/mi mice 2 SummaryTo elucidate the effects of teeth on muscle fibers in tongue during the development process, we examined the expression of muscle contractile proteins and the genes for those proteins in normal mice and microphthalmic (mi/mi) mice with impaired tooth eruption. The mice were observed during the growth period, including weaning, which is when feeding movements undergo major changes.Expression of the myosin heavy chain (MyHC)-2a protein, whose contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Such heterogeneity in the site and stage of expression suggested progressive maturation of the muscle fiber attachments. Expression of the myosin heavy chain (Gojo et al 2002;Usami et al 2003;Maejima et al 2005;Shida et al 2005;Okubo et al 2006;Yanagisawa et al 2006;Abe et al 2007;Suzuki et al 2007;Yoshii et al 2008) appeared to have been completed before that of desmin was initiated. Likewise, silver impregnation showed that the endomysium of each muscle fiber was apparently in tight contact with the perichondrium, insertion tendon or intramuscular tendon until the expression of desmin appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Such heterogeneity in the site and stage of expression suggested progressive maturation of the muscle fiber attachments. Expression of the myosin heavy chain (Gojo et al 2002;Usami et al 2003;Maejima et al 2005;Shida et al 2005;Okubo et al 2006;Yanagisawa et al 2006;Abe et al 2007;Suzuki et al 2007;Yoshii et al 2008) appeared to have been completed before that of desmin was initiated. Likewise, silver impregnation showed that the endomysium of each muscle fiber was apparently in tight contact with the perichondrium, insertion tendon or intramuscular tendon until the expression of desmin appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Sartorius et al [ 13 ] reported that skeletal muscles in myosin heavy chain-IId-null mice show increased levels of myosin heavy chain-IIa (MHC-IIa). Yanagisawa et al [ 14 ] have also reported that the presence of MHC-IIa after weaning in microphthalmic (mi/mi) mice with no tooth eruption was attributable to compensation for a lack of proper masticatory function and sucking-like movements, as MHC-IIa is necessary for these movements. In other words, muscle fibers change according to muscle function and structure, and therefore an understanding of the composition of MHC is important when considering the function of the suboccipital muscles.…”
Section: Introductionmentioning
confidence: 99%
“…As primary antibodies, SC-71 (antiMyHC-2a) and BF-F3 (anti-MyHC-2b) (American Type Tissue Culture), anti-mouse monoclonal antibodies extracted from hybridoma cells, were used 10,[14][15][16]23) . More specifically, after culturing the hybridoma cells in DMEM (10% FBS) medium at 37°C and 5% CO 2 for 72 hours, they were centrifuged, and the supernatants were used as antibodies.…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
“…Maejima et al and Yanagisawa et al examined the changes of the muscle fiber characteristics of the upper and lower halves of the adult mouse tongue muscle before and after weaning, and confirmed marked changes of isoforms 15,16) . Thus, marked functional changes before and after weaning, i.e., from suckling to chewing, were demonstrated to influence the characteristics of muscle fibers in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation